Práctica profesional Escuela José María Roy - Batista Guerra, Yazmina María (David, Panamá : UDELAS, 2009)
The importance of this work is to reproduce the journey of a degree in teaching english from the perspective of learning by using the vrious skills acquired durind this time and including the students in developing themselves so they can see opportunites offered by english as a secon languaje.
General index Graphic index Introduction Chapter I Chapter II Background Definition and characteristics of professional practice Selection or evaluation criteria Value of the subject with their specialty Objectives of the professional practice General objectives and specific objectives Target population Direct and indirect Activities during the professional practice Diagnstic - graphics Intervention Results - graphics Resources Timetable 23, 24, 25 Chapter III Analysis and interpretation of results Relevant consideration Conclusion References Annexes
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Ingles
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- INFORME DE PRACTICA DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN ESPECIAL; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; ESCUELA JOSÉ MARÍA ROY - CHIRIQUÍ